Influence of the properties of filler on high and medium temperature performances of asphalt mastic. (15th August 2016) - Cheng, Yongchun; Tao, Jinglin; Jiao, Yubo; Tan, Guojin; Guo, Qinglin; Wang, Shurong; Ni, Ping
Highlights: Four fillers including limestone, hydrated lime, fly-ash and diatomite are studied. Five tests are conducted on fillers and four tests are conducted on asphalt mastics. The high/medium temperature performances of DAM are better than that of LAM, HLAM and FAM. Correlation degrees between properties of filler and performances of mastic are studied. SSA is expected to be the most influential property on performances of asphalt mastic. Abstract: Filler is the main component of asphalt mastic and its properties are closely associated with the performances of asphalt mastic. To investigate the relationship between properties of fillers and performances of asphalt mastic, four fillers including limestone, hydrated lime, fly-ash and diatomite were selected to prepare corresponding asphalt mastics. The density, specific surface area, particle size distribution, mineralogy component and hydrophilic coefficient of fillers and softening point, viscosity, force ductility and dynamic rheological property of asphalt mastics with different fillers were tested. Grey relational analysis (GRA) method was employed to determine the correlation degree between properties of fillers and high/medium temperature performances of asphalt mastics. Results showed that four fillers presented differences in density, specific surface area, mineralogy component and hydrophilic coefficient. Besides, softening point, viscosity, deformation energy and complex modulus of diatomite asphalt mastic were higher than that of other three filler-asphalt systems. Furthermore, specific surface area was suggested to be the most influential property on the high and medium temperature performances of asphalt mastic in comparison with other properties based on the results of GRA.